EVALUASI PROSEDUR PELAKSANAAN PEMBERIAN TUNJANGAN KEPADA KARYAWAN DI PT BRI TBK CABANG â€œXâ€ - ALESTI, AVELINE FIRSTY (Universitas Katolik Widya Mandala Surabaya, 2012)
PT Bank Rakyat Indonesia (Persero) Tbk. Surabaya Kaliasin branch office has operational support section, which become one of supporting unit in the company. This Section consist Secretariat and HRD. HRD has a function on the fulfillment of workers welfare and right which is employee allowances or benefit as per regulation being decided by formal Decision Letter. Benefits given to employee are medical, on leave and transportation allowance for business trip. In order to get that kind of benefits, the employee should request it trough specific procedure and fulfill all documentation needed as decided in specific Decision Letter. The Decision Letter being used as a control tool on the effectiveness of allowance distribution and also to prevent the company from the risk of miss used and potential problem which of company operation. The type of thus research is explanatory case studies. The apprentice will do the observation and looking at on written documentation, in order to get full picture about company operational activities and also getting some deeper information as well as the control trough questioners. The outcome will be evaluated and analyzed properly. As the results of evaluation an allowances distribution (medical, on leave, an transportation). The outcome shows the implementation has being managed properly as per regulation which been consisted into specific Decision Letter.